[OP.4D.04] METABOLOMIC STUDY OF THE EFFECT OF UROMODULIN ON BIOCHEMICAL PATHWAYS IN THE KIDNEYS. (September 2016) - Graham, L.; Graham, D.; McBride, M.W.; Dominiczak, A.F.; Padmanabhan, S.
Abstract : Objective: UMOD−/− mice have low blood pressure and decreased salt-sensitivity indicating interactions between UMOD and sodium transport. However, it's unclear whether the effect of UMOD is solely through interaction with cognate molecules in the TAL or whether the perturbations in physiology are more complex with involvement of the TAL and other parts of the nephron. We propose to answer this by metabolomic profiling of renal tissue from UMOD+/+ and UMOD−/− mice. Design and method: UMOD+/+ and UMOD−/− male mice of 12 weeks of age were treated ± 2% NaCl ad libitum in the drinking water for 6 weeks (n = 5 per group). Following the stimulation period mice were sacrificed, and both kidneys excised for metabolic analysis; one kidney was dissected and outer medulla tubules removed, the other kidney remained whole. Global biochemical profiles were determined in both tissue matrices (Metabolon Inc). ANOVA contrasts were used to identify biochemicals that differed significantly (p0.05) between experimental groups. An estimate of the false discovery rate (q-value) is calculated to take into account the multiple comparisons. Results: Lipid and lipid metabolites were prominently altered in UMOD−/− mice. The protein glycosylation substrates UDP-galactose, UDP-N-acetylglucosamine and UDP-N-acetylgalactosamine were elevated in UMOD−/− whole kidney under normal-salt and salt-load conditions. Bile acids were significantly lower in UMOD−/− in both whole kidney and outer medulla samples. The most significant salt-load dependent change in UMOD−/− mice was an increase in 13-hydroxyoctadecadienoic acid + 9-hydroxyoctadecadienoic acid in UMOD−/− in outer medulla. The endocannabinoids palmitoyl ethanolamide and oleoyl ethanolamide were elevated in UMOD−/− medulla, while arachidonoyl ethanolamide was lower in UMOD−/− outer medulla. Conclusions: This study is the first to investigate metabolic profiles in UMOD−/− mice (±2% NaCl). We found UMOD−/− disrupts lipid signalling in kidney and outer medulla, suggesting a mechanism that influences kidney metabolite excretion and/or reabsorption. Higher levels of protein glycosylation precursors signify changes in secreted protein synthesis rates. Additionally, 13-HODE and 9-HODE alteration in UMOD−/− mice impact glomerular filtration rate. Understanding the effects of the altered UMOD expression on urinary excretion and plasma metabolite levels may offer insights into the various effects of the protein on sodium homeostasis.